Faktor-Faktor yang Berhubungan dengan Self Care Management Pada Pasien Hipertensi di Puskesmas Kabawetan - Fernalia Fernalia; Buyung Keraman; Rahmad Satrio Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the factors associated with self-care management in hypertensive patients at the Kabawetan Public Health Center. The method used in this study is a quantitative study with an analytical survey design using a cross-sectional research design. The results showed that from 42 hypertensive patients, the majority of respondents with good self-care management were 24 people (57.1%), 14 people (33.3%) with poor knowledge, 22 people (52.4%) with individual scores. Good, and 25 people (59.5%) with good self-efficacy. The results of the bivariate analysis showed that the p-value <0.05. In conclusion, there is a significant relationship between knowledge, individual values, and self-efficacy with the self-care management of hypertensive patients at the Kabawetan Public Health Center. Keywords: Self-Efficacy, Values, Knowledge, Self Care Management